Power Electronic Architecture for Multi-Vehicle Extreme Fast Charging Stations - (:unkn) unknown (My University, 2020)
Electric vehicles (EV) are quickly gaining popularity but limited driving range and a lack of fast charging infrastructure are preventing widespread use when compared with gas powered vehicles. This gave rise to the concept of multi-vehicle extreme fast charging (XFC) stations. Extreme fast charging imposes challenges in the forms of power delivery, battery management, and energy dispatch. The extreme load demand must be handled in such a way that users may receive a timely charge with minimal impacts on the electric grid. Power electronics are implemented to address these challenges with highly power dense and efficient solutions. This work explores a power electronic architecture as one such solution. The system consists of three parts: a cascaded H-bridge (CHB) active rectifier that interfaces to a medium voltage (MV) grid, a dual active bridge (DAB) based solid state transformer (SST) that provides isolation and forms a low voltage DC (LVDC) bus, and full bridge DC-DC converters configured as partial power converters (PPC) that interface with the vehicle battery.